Queixas técnicas e eventos adversos a medicamentos notificados em um hospital sentinela do interior de São Paulo, 2009-2010 - Lima, Paula Ferraz De; Cavassini, Ana Claudia Molina; Silva, Flavia Aparecida Toledo; Kron, Meline Rossetto; GonÇalves, Simone Fernanda; Spadotto, Ariadne; Lima, Silvana Andréa Molina [UNESP] (FapUNIFESP (SciELO), 2013)
Objective: to describe technical complaints and adverse drug events reported in a sentinel hospital in São Paulo state in 2009 and 2010. Methods: This is a descriptive study. Information was obtained from the sentinel hospital Risk Management database. Results: we found 199 reports related to drugs: 70.0% were technical complaints, 21.0% ineffective therapy and 9.0% adverse reaction to medication. The pharmacological groups with highest number of reports were: drugs that act on alimentary tract and metabolism (25.1%), the nervous system (25.1%) and anti-infective drugs for systemic use (22.1%). Conclusion: technical complaints and adverse drug events were frequent, despite recognized underreporting. The characterization of these events could inform the adoption of control measures and permanent educational actions in health services in order to prevent their occurrence.

Objetivo: descrever queixas técnicas e eventos adversos a medicamentos notificados em hospital sentinela no interior do estado de São Paulo, Brasil, incluindo todas as notificações realizadas nos anos de 2009 e 2010. Métodos: trata-se de estudo descritivo, a partir de informações obtidas do banco de dados da Gerência de Risco do hospital sentinela. Resultados: foram realizadas 199 notificações relacionadas a medicamentos, sendo 70,0% de queixas técnicas, 21,0% por ineficácia terapêutica e 9,0% por reações adversas a medicamento; os grupos farmacológicos com maior número de notificações foram drogas com ação sobre o aparelho digestivo e metabolismo (25,1%), sobre o sistema nervoso (25,1%), e anti-infecciosos gerais para uso sistêmico (22,1%). Conclusão: as queixas técnicas e eventos adversos a medicamentos foram frequentes, apesar da reconhecida subnotificação; a caracterização desses eventos pode subsidiar a adoção de medidas de controle e ações de educação permanente nos serviços de saúde, voltadas a sua prevenção.
Technical complaints and adverse drug events reported in a sentinel hospital in the state of São Paulo, 2009-2010
Keywords: Pharmacovigilance; Medication Systems Hospital; Adverse Drug Reaction Reporting Systems; Drug Toxicity; Epidemiology; Descriptive.; Farmacovigilância; Sistema de Medicação no Hospital; Sistemas de Notificação de Reações Adversas a Medicamentos; Toxicidade de Drogas; Epidemiologia Descritiva.